Effects of iLearning Media on Student Learning Motivation - Aini, Qurotul; Dhaniarti, Iswachyu; Khoirunisa, Alfiah (APTISI Transactions on Management (ATM), 2019)
As we know today, Indonesia has entered the era of revolution 4.0 which in that era had a major influence on the changes that took place in all fields. Including in the field of education, in particular, the changes that occur in the world of education today are so rapid with the abandonment of learning methods that still use conventional methods. Doing tasks with books, face-to-face communication, collecting assignments in hard copy, which will certainly cause a lot of losses in a certain period of time, such as many assignments that are long buried and difficult to find when needed. This method is certainly considered a boring and time-consuming method, where students cannot explore in the learning process which will take a long time to do a manual search for the number of files that have been collected. At present, the application of learning methods with concepts organizes many reports on the work of assignments on a website content management system. This learning method is made to maximize the way to organize student assignment reports for time management efficiency, therefore this learning method can be applied as the management of education in higher education. It is expected that the existence of this method can improve time management in learning so that it motivates to explore abilities in the existing learning process